Analisis Penerapan Total Productive Maintenance (TPM) dengan Perhitungan Overall Equipment Effectiveness (OEE) pada Mesin Sewing (Studi Kasus: CV. Bebetrend Garment) - Najma Murti Fadlika; Indah Wahyu Utami; Pitoyo Amrih (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
CV. Bebetrend Garment Sukoharjo is a garment company whose core process lies in the sewing department. Observations of three sewing machines (two collar-attaching machines and one sleeve-hemming machine) during May–June 2026 revealed considerable downtime, unstable production speed, and a notable level of defective output. This study aims to measure sewing machine effectiveness using the Overall Equipment Effectiveness (OEE) method and to identify the dominant causes of loss through Six Big Losses analysis within a Total Productive Maintenance (TPM) framework. The research employed a quantitative descriptive approach using primary and secondary data obtained through observation, interviews, and company production records. The results show that the OEE values of the three machines ranged from 63% to 70%, well below the world-class standard of 85%, with availability (82.5%–85.2%), performance (80.7%–87.7%), and quality rate (95%–96%) all falling short of JIPM standards. Six Big Losses analysis identified reduced speed losses as the largest contributor, averaging 11.15%–17.20%, followed by breakdown losses averaging 9.06%–10.46%.